PERAN ENVIRONMENTAL PERFORMANCE TERHADAP ENVIRONMENTAL DISCLOSURE DAN ECONOMIC PERFORMANCE - Yendrawati, Reni; Tarusnawati, Lalitya Reni (Jurnal Keuangan dan Perbankan, 2013)
This study aimed to determine the effect of environmental performance on environmental disclosure andeconomic performance, and also the effect of environmental disclosure on economic performance. The data wastaken from the annual report of 2009-2011companies listed on the Indonesian Stock Exchange and participatingin PROPER. This study used multiple regressions. Environmental performance results showed there wasa significant positive effect on environmental disclosure, environmental disclosure and there was a significantpositive effect on economic performance, and the environmental performance did not significantly affect theeconomic performance. Environmental performance had indirect influence on economic performance.